Application of Artificial Intelligence in the Economic Sphere - Dilmuradov T.S; Uralov E.A; Jurakulov A.F; Khodjaev M.O (Zien Journals, 2023)
The use of information processing tools is a new step in improving business efficiency through the introduction of modern technologies, including digital transformation tools. The use of artificial intelligence systems makes it possible to operate with huge memory arrays, which is relevant for the financial sector. Using machines to make managerial decisions, to optimize customer service, calculate the effectiveness of investments without the impact of the human factor or its minimization means making decisions based only on information without a personal approach, which often leaves a negative imprint. The advantage of using artificial intelligence now is that data collection does not stop and the larger the database, the more efficient the system, therefore, those banks that postpone the decision to implement artificial intelligence systems in their work risk not catching up with more knowledge-intensive competitors.
Keywords: artificial intelligence; bank; efficiency; globalization